Individual Factors of Health Seeking Family Behavior Caring for Mental Illness with Physical Restraint (Physical Restraint) in Manggarai Regency: Descriptive Study - Reong, Antonia Rensiana; Devy, Shrimarti Rukmini; Efendi, Ferry (International Journal of Psychosocial Rehabilitation, 2020)
Health seeking behavior (HSB) has been defined as any action or absence of action taken by individuals who consider themselves to have health problems or illness for finding the right medicine. Poor availability and access to basic mental health services in Indonesia has not been satisfactory, resulting in an impact on the problem of unfinished physical restraint (Physical restraint) action. The purpose of this study is directed to an understanding of the description of the level of personal understanding of the family of the patient mental illness that is put in place and how the family HSB attempts to care for these patients (individual factors). This study uses a descriptive qualitative approach method. These are eight families of mental illness patients who are caring for mental patients in physical restraint. In this study, the researcher used non-probability sampling with snowball sampling technique and then the data were analyzed by the thematic method. The result of this study indicates that the information and handling of patients by the family mostly only focus on traditional medicine. Ef orts of family seeking health behavior in caring for patients with physical restraint (physical restraint) are more influenced by individual factors. It was caused by lack of knowledge and information about mental health, self-medication due to shame and stress, and traditional medicine is influenced by the mindset of mystical elements in family behavior in caring for patients.